A New Hieratic Ostracon from Lachish - Wimmer, Stefan Jakob (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
A fragmentary ostracon, inscribed in Egyptian hieratic and found by the Austrian team during renewed excavations at Lachish, can safely be dated to the early (pre-Amarna) 18th dynasty. Albeit difficult to read, it seems to preserve part of a list with apparently Canaanite names and allocated provisions, in a structured layout. This differs notably from the later (Ramesside) hieratic inscriptions from Lachish and provides important evidence for early scribal practice and Egyptian involvement at the site in the 15th century BC.